Management of melanoma patients during COVID‐19 pandemic in an Italian skin unit. Issue 3 (8th March 2021) - Filoni, Angela; Del Fiore, Paolo; Cappellesso, Rocco; Dall'Olmo, Luigi; Salimian, Nick; Spina, Romina; Tropea, Saveria; Rastrelli, Marco; Russano, Francesco; D'Amico, Mattia; Collodetto, Alessandra; Rossi, Carlo Riccardo; et al.
Abstract: Due to the COVID‐19 crisis, many scheduled medical and surgical activities have been suspended. This interruption to the healthcare system can negatively affect the diagnosis and management of melanoma. Neglecting melanoma throughout the outbreak may be associated with increased rates of mortality, morbidity, and healthcare expenses. We performed a retrospective review of all dermatological and surgical activity performed in our Melanoma Skin Unit between 23 February 2020 and 21 May 2020 and compared these data with those from the same period in 2019. During the lockdown period, we observed a decrease in dermatologic follow‐up (DFU) (−30.2%) and in surgical follow‐up (SFU) (−37%), and no modification of melanoma diagnosis (−3%). Finally, surgical excisions (SE) (+ 31.7%) increased, but sentinel lymph node biopsy (SLNB) (−29%) and lymph node dissections(LND) (−64%) decreased compared to the same period in 2019. Our experience supports the continuation of surgical and diagnostic procedures in patients with melanoma during the COVID‐19 pandemic. Surgical and follow‐up procedures for the diagnosis and treatment of melanoma should not be postponed considering that the pandemic is lasting for an extended period.